DEBT RATIO, PERFORMANCE AND CORPORATE VALUES: MANAGERIAL OWNERSHIP VERSUS NON- MANAGERIAL OWNERSHIP - Hartiny Pop Koapaha (UNKLAB Business School, 2020)
This study aims to determine the comparison of debt ratio, company performance and value between companies with managerial ownership and non-managerial ownership companies. The method used in this research is descriptive method and different test using independent sample t- test tools. The number of samples in this study were 180 companies consisting of 14 companies with managerial ownership and 166 non-managerial ownership companies. The results show that the value of debt ratio (debt ratio), financial performance and the value of companies with managerial ownership are higher than non-managerial ownership companies. However, the results of hypothesis testing for significance value when tested with the independent sample t test method found that only the value of debt ratio or related debt ratio that there are significant differences between companies with managerial ownership when compared with non-managerial ownership companies. For financial performance and firm value variables, it is found higher in companies with managerial ownership, but it was not found to be significantly different when compared to company performance and non-managerial ownership companies. Keywords: Company value, debt ratio, managerial ownership